Challenges and strategies for implementing Chinese medicine during COVID-19 in Malaysia - Chiah Shean Teo; Pik Munn Tan; Connie Siew Ing Shu; Zi Xian Choo; Kian Keong Te (Integrative Medicine Research)
Background: Implementing Chinese medicine (CM) for COVID-19 in Malaysia is challenging for local CM practitioners. The successful experience of CM in China can only be partially adopted in Malaysia due to differences in the national health care system and legislation, geographical health disparities and cultural diversity. Despite all the challenges, Malaysian CM practitioners have managed to thrive and found a Malaysian CM solution amid COVID-19. Methods: A literature review was conducted using various databases and gray literature from inception to August 15, 2021, to evaluate the challenges faced by Malaysian CM practitioners and the corresponding strategies in Malaysia's country context during COVID-19. Results: A total of 9 challenges and issues faced by Malaysian CM practitioners during COVID-19 were identified. Their corresponding strategies were further categorized into 3 phases, namely, preparation, development and implementation. The strategies were appraised using the SWOT analysis method, and 17 factors were identified. Strength analysis includes personalized CM prescriptions with online consultations in Malaysia. Limited research input for CM in COVID-19 and the inadequate research capacity of local CM institutions are discussed in threat analysis. Conclusion: Various approaches have been implemented by Malaysian CM practitioners to provide safe, qualified and effective CM services for COVID-19 at the community level, aiming to reduce the national health care burden. A public-private partnership initiative can bridge the knowledge gap and optimize the role of CM in the health emergency system. This Malaysian CM solution can provide insights to interested countries to capitalize on the potential contribution of Traditional and Complementary Medicine (T&CM) in the era of COVID-19.